2005
DOI: 10.1177/1087054705280413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of ADHD Symptoms in the National Health Interview Survey

Abstract: ADHD symptoms vary by race and ethnicity, gender, and age and are associated with other emotional and behavioral difficulties. Both overdiagnosis and underdiagnosis of ADHD may be issues in the U.S. population of 4- to 17-year-olds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
156
5
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(191 citation statements)
references
References 40 publications
18
156
5
2
Order By: Relevance
“…Thus it is unknown whether those with ADHD were more or less likely to participate in the survey, although the age trends and relationships found in Table 1 between ADHD symptoms and more comorbidities and other difficulties, are consistent with many other studies (e.g. Able et al2007;Brassett-Harknett and Butler 2007;Cuffe et al 2005;Faraone et al 2005) and serve to validate the ADHD self-report construct in a community sample.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Thus it is unknown whether those with ADHD were more or less likely to participate in the survey, although the age trends and relationships found in Table 1 between ADHD symptoms and more comorbidities and other difficulties, are consistent with many other studies (e.g. Able et al2007;Brassett-Harknett and Butler 2007;Cuffe et al 2005;Faraone et al 2005) and serve to validate the ADHD self-report construct in a community sample.…”
Section: Discussionsupporting
confidence: 65%
“…Historically, ADHD was viewed as a diagnosis for children and adolescents as it was believed to diminish before adulthood (Goodman 2007). However, followup studies during the last 30 years have added ADHD to the range of adult psychiatric conditions, although evidence suggests that the number and severity of symptoms decline with age (Cuffe et al 2005;Faraone et al 2005). Diagnosis of ADHD is further complicated by the higher presence of comorbidities, such as mood, anxiety, conduct (CD), oppositional defiant (ODD), anti-social personality and substance use disorders in persons with diagnosed ADHD when compared to normal controls (Asherson et al 2007; Kessler et al 2006;Secnik et al 2005;Weiss et al 1985;Young et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with multiple epidemiological studies. 3,7,29 The inattentive subtype emerged as the most prevalent subtype in our study as compared to combined subtype in some clinicbased studies. This implies that females and the inattentive subtype are under-diagnosed and/or under-treated in the community.…”
Section: Discussionmentioning
confidence: 51%
“…[4][5][6] This variability may be due to methodological issues, such as differences in diagnostic criteria, sample ascertainment, developmental stages, tools of assessment, and rater bias. Some recent population-based studies that do not use DSM-IV criteria have reported prevalence of ADHD either close to DSM-IV estimates 7 or much higher. 8 In a recent review, Rowland and colleagues conclude that lack of large population-based epidemiologic studies limits the understanding of this disorder and that further studies are needed to ascertain the true prevalence of ADHD in the community.…”
Section: Introductionmentioning
confidence: 89%